Avaliação das variáveis cardiovasculares, capacidade de caminhar e nível de atividade física de obesos mórbidos antes e depois da cirurgia bariátrica - Lopes, Thiago Jambo Alves (2010)
Morbidly obese patients present an increase in heart rate, blood pressure and perceived exertion besides lower walking ability compared to normal weight people. However, little is known about how these variables are presented after bariatric surgery. Moreover, despite the distance walked during the six-minute walk (6MWT) improve after surgery is not well established if the level of physical activity influences this improvement. Objective: To evaluate cardiovascular performance, perceived effort, ability of walking and physical activity level of patients with morbid obesity before and after bariatric surgery. Methods: The cardiovascular performance, perception of effort, the ability to walk and level of physical activity were assessed in 22 patients before (BMI = 50.4 kg/m2) and after (BMI = 34.8 kg/m2) bariatric surgery through the 6MWT. The heart rate, blood pressure and perceived exertion were assessed at rest, at the end of the 6MWT and in the second minute post-test (HR recovery). The ability to walk was measured by total distance walked at the end of the test while the level of physical activity was estimated by applying the Baecke questionnaire, analyzing domains occupation, leisure and locomotion and leisure and physical activity. Results: The HR at rest and recovery decreased significantly (91.2 ± 15.8 bpm vs. 71.9 ± 9.8 bpm, 99.5 ± 15.3 bpm vs 82.5 ± 11.1 bpm, respectively), as well as all the arterial pressure and perceived exertion after surgery. The distance achieved by the patients increased by 58.4 m (p = 0.001) postoperatively. Time postoperatively had correlation with the percentage of excess weight lost (r = 0.48, p = 0.02), BMI (r =- 0.68, p = 0.001) and the Baecke (r = 0.52, p = 0.01) which did not happen with the distance walked (r = 0.37, p = 0.09). Despite weight loss, patients showed no difference in the level of physical activity in any of the areas before and after surgery. Conclusion: The cardiovascular performance, the perception of effort and ability to walk seem to improve after bariatric surgery. However, despite improvement in the ability to walk by the distance achieved in the 6MWT after weight loss, this is not reflected in an increase in physical activity level of obese patients after surgery